Phylogenetic analysis of some Sporomusa sub-branch members isolated from human clinical specimens: description of Megasphaera micronuciformis sp. nov - Marchandin, Helene; Jumas-Bilak, Estelle; Gay, Bernard; Teyssier, Corinne; Jean-Pierre, Helene; Simeon de Buochberg, Michele; Carriere, Christian; Carlier, Jean-Philippe (International journal of systematic and evolutionary microbiology, 2003)
1 Laboratoire de Bactériologie, Hôpital Arnaud de Villeneuve, 371 Avenue du doyen Gaston Giraud, F-34295 Montpellier Cedex 5, France 2 Laboratoire de Bactériologie, Faculté de Pharmacie, F-34060 Montpellier Cedex 2, France 3 Centre National de Référence des Bactéries Anaérobies, Institut Pasteur, 25 rue du Dr Roux, F-75724 Paris Cedex 15, France Correspondence Hélène Marchandin h-marchandinatchu-montpellier.fr Two unknown, Gram-negative, catalase-negative and strictly anaerobic cocci were isolated from two independent human samples (strains AIP 49.01 and AIP 412.00 T ). Comparative 16S rRNA gene sequencing demonstrated that these two organisms displayed 99·8 % sequence identity and that they are members of the Sporomusa sub-branch of the low-G+C Gram-positive bacteria. The most closely related 16S rDNA sequences were from Megasphaera sp. oral clone BU057 (99·8 %) and from isolates of Megasphaera cerevisiae and Megasphaera elsdenii (94·5 and 93·8 %, respectively). Phylogenetic analysis based on 16S rDNA sequences showed that these two strains were most closely related to M. elsdenii and belonged to the Megasphaera genus. Differences from previously described Megasphaera species in terms of size, biochemical tests (particularly the analysis of metabolic end products), gas production and DNA G+C content indicated that the two strains studied represent a novel species of anaerobic Gram-negative cocci. The name Megasphaera micronuciformis sp. nov. is proposed for these two isolates. It is also proposed that the uncultured organism previously deposited as Megasphaera sp. oral clone BU057 should be named Candidatus Megasphaera micronuciformis. The type strain of Megasphaera micronuciformis is AIP 412.00 T (=CIP 107280 T =CCUG 45952 T ). Abbreviations: EM, electron microscopy Published online ahead of print on 23 August 2002 as DOI 10.1099/ijs.0.02378-0. The GenBank/EMBL/DDBJ accession numbers for the 16S rDNA sequences of Megasphaera micronuciformis AIP 49.01 and AIP 412.00 T are AF473833 and AF473834 , respectively. A full version of the phylogenetic dendrogram is available as supplementary data in IJSEM Online ( http://ijs.sgmjournals.org ).